Gendered difference in motivational profiles, achievement, and STEM aspiration of elementary school students - Olive, Kezia; Tang, Xin; Loukomies, Anni; Juuti, Kalle; Salmela-Aro, Katariina (Frontiers in Psychology, 2022)
To better understand the gender gap in STEM (Science, Technology, Engineering and Math) aspiration, the article examines the critical role of domain-specific motivation (i.e., expectancy and task values). Using longitudinal data from 5th and 6th grade (~11-12-year-old) students (n= 360, 55% girls), person-oriented analyses was applied to understand the gendered motivational profiles and their longitudinal influence on achievement and STEM aspiration. Specifically, we aimed to (1) derive motivational belief profiles regarding science, mathematics, and language (Finnish), (2) analyze the stability and change in the profiles between the 5th and 6th grade, (3) assess the relationship between motivational profiles and achievement and STEM aspiration, and (4) test for gender differences. We derived four motivational profiles for both years: high motivation in all subjects (~21%), high mathematics motivation (~46%), low mathematics motivation (~11%), and low motivation in all subjects (~8%). Latent transition analysis revealed that most students remained in the same profile throughout the two years. We found evidence of gendered differences in the motivational profiles and the chance of transitioning between profiles. More girls are characterized by low math motivation, while boys are more likely to transition to higher math motivation in 6th grade. The motivational difference is reflected in their achievement, although not strongly coupled with their STEM aspiration. The findings suggest that at this developmental stage, Finnish students have not developed a strong association between (gendered) STEM aspiration and their domain-specific motivation, although their motivation may have influenced their achievement. Interpretation and practical implications are discussed.